MEMBERDAYAKAN KEPRIBADIAN PESERTA DIDIK MELALUI PENDEKATAN QUANTUM LEARNING - Afiful Hair (Fakultas Agama Islam Universitas Islam Madura, 2020)
In addition to the knowledge society and learning society, the 21st century is often referred to as the mega era of competition. Therefore, a measure of the success and existence of someone is determined by the ability to compete and the quality they have. Humans have tremendous abilities, both physically, intellectually, and mentally spiritually. If this potential is successfully developed proportionally through a good educational process, it will give birth to perfect humans, humans who excel in the